Single-cell expression profiling reveals a dynamic state of cardiac precursor cells in the early mouse embryo - Kokkinopoulos, Ioannis; Ishida, Hidekazu; Saba, Rie; Ruchaya, Prashant [UNESP]; Cabrera, Claudia; Struebig, Monika; Barnes, Michael; Terry, Anna; Kaneko, Masahiro; Shintani, Yasunori; Coppen, Steven; Shiratori, Hidetaka; et al. (Public Library Science, 2015)
In the early vertebrate embryo, cardiac progenitor/precursor cells (CPs) give rise to cardiac structures. Better understanding their biological character is critical to understand the heart development and to apply CPs for the clinical arena. However, our knowledge remains incomplete. With the use of single-cell expression profiling, we have now revealed rapid and dynamic changes in gene expression profiles of the embryonic CPs during the early phase after their segregation from the cardiac mesoderm. Progressively, the nascent mesodermal gene Mesp1 terminated, and Nkx2-5+/Tbx5+ population rapidly replaced the Tbx5low+ population as the expression of the cardiac genes Tbx5 and Nkx2-5 increased. At the Early Headfold stage, Tbx5-expressing CPs gradually showed a unique molecular signature with signs of cardiomyocyte differentiation. Lineage-tracing revealed a developmentally distinct characteristic of this population. They underwent progressive differentiation only towards the cardiomyocyte lineage corresponding to the first heart field rather than being maintained as a progenitor pool. More importantly, Tbx5 likely plays an important role in a transcriptional network to regulate the distinct character of the FHF via a positive feedback loop to activate the robust expression of Tbx5 in CPs. These data expands our knowledge on the behavior of CPs during the early phase of cardiac development, subsequently providing a platform for further study.